Uncertain night the studio as a mythical-symbolic experience (Revista Apotheke, 2023)
Every day, when I arrive at my studio, I enter an alternative reality which I named Omphalos or 2070. I experience it as an archaeological site, from which images of a vaguely recognizable future reality sprout. However, this simulacrum contains a whole set of possible discourses on painting, developed by me, as an author, always in the first person.
Keywords: Studio; Painting; Alchemy; Faith